The upcoming psychological forum has already made it into history of the European psychological congresses - Aleksandr N. Veraksa; Anna V. Leybina; Sergey V. Leonov (Национальный психологический журнал, 2019)
6th European Psychological Congress(July 2–5, 2019 Moscow)